2015
DOI: 10.1097/meg.0000000000000315
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic yield of preoperative staging computed tomography of the thorax in colorectal cancer patients without hepatic metastases

Abstract: In the absence of liver metastases, CRC rarely spreads to the lung. Consequently, preoperative chest CT examination for patients without evidence of liver metastases may not be necessary in the majority of patients. Future studies are required to identify patients at high risk for pulmonary metastases who may benefit from this preoperative investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Most guidelines agree that the chest should be imaged for staging of CRC, but there is disagreement about the exact type of imaging modality (11). The National Comprehensive Cancer Network has recommended CT rather than plain film radiographic imaging of the chest (12).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most guidelines agree that the chest should be imaged for staging of CRC, but there is disagreement about the exact type of imaging modality (11). The National Comprehensive Cancer Network has recommended CT rather than plain film radiographic imaging of the chest (12).…”
Section: Discussionmentioning
confidence: 99%
“…The National Comprehensive Cancer Network has recommended CT rather than plain film radiographic imaging of the chest (12). The main reason for the use of CT for staging is early diagnosis of pulmonary metastases with high sensitivity of 51% to 73% and specificities of up to 74%, which increases the rate of resection of pulmonary metastasis (4,11). CCT is competent for identifying nodules of 2 -3 mm, whereas CXR identifies lesions 5-10 mm in size (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While ESMO guidelines suggest a CT scan of the abdomen and pelvis, without chest imaging, NCCN recommends contrast enhanced imaging of the chest [32,33]. In patients without hepatic metastasis, the rate of isolated pulmonary metastasis is extremely low at 1.4-6.3%, suggesting a relatively low yield for chest imaging [34][35][36]. A meta-analysis of 5873 patients demonstrated that although 9% of patients will be found to have an indeterminate nodule on chest imaging, only 10.8% of these will turn out to be metastatic colorectal metastasis, once again indicating a relatively low yield in the face of extensive work up that will be undertaken by many patients to evaluate indeterminate findings [37].…”
Section: Historical Overviewmentioning
confidence: 99%
“…The benefit of staging chest CT can be measured in terms of diagnostic yield (DY) and false-referral rate (FRR), which indicate the proportions of patients with true-positive metastases and false-positive metastases, respectively (8,9). There have been studies that reported DY or FRR of staging contrastenhanced chest CT, but all those studies stratified their patients by pathologic stage, which is frequently unavailable at the time of initial diagnosis and treatment planning (10,11). We hypothesized that the value of staging contrast-enhanced chest CT in patients with colon cancer may differ across clinical stage determined from contrast-enhanced abdominal CT. Our study aimed to measure DY and FRR of staging contrast-enhanced chest CT based on the clinical stage from contrast-enhanced abdominal CT in patients with colon cancer.…”
mentioning
confidence: 99%